Exploring the Use of Wh-Questions for Reading Comprehension Text at a Rural-Based Secondary School - Nephawe, Farisani Thomas (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
Questioning is a fundamental skill in communication because it elicits a productive and accurate response. However, it poses challenges to English second language learners living in deep rural traditional villages. The paper explored the use of wh-questions in reading comprehension text by Grade 10 English First Additional Language learners at Milton Mpfumedzeni Secondary School at the Vhumbedzi Circuit in Limpopo Province, South Africa. A quantitative approach was adopted because it uses statistics and numbers to predict, discover facts, and test hypotheses while the qualitative provides in-depth knowledge of a phenomenon. Thirty-six participants were selected using a simple random sampling technique because it gives each member of the population an equal chance of being included in the investigation. Also, a convenience sampling procedure was utilised as the subjects are readily accessible although participation is not equal for all members of individuals in the target population and study results are not essentially generalisable. The Statistical Package for Social Sciences Version 22 to maintain in-depth statistical analysis due to its feasibility. Preliminary investigation revealed that participants were incompetent in reading comprehension text but after using momentous strategies, they performed outstandingly. Thus, the paper sanctions using the identified strategies applicable to reading comprehension text.